Innovative Strategy for Sustainable Business Model Development with Value and Social Impact Approach for Economic Sustainability - Ibrahim, Fachmi (PT. LITERASI SAINS NUSANTARA, 2023)
Economic sustainability has become a primary concern in addressing global challenges. Confronting the complexity of economic sustainability challenges, innovation and the development of sustainable business models are crucial. This research aims to identify, develop, and test innovative strategies for sustainable business model development with a focus on value and social impact. The study employs a comprehensive examination of previously published works, utilizing qualitative analysis to achieve a holistic understanding of the topic, spanning the timeframe from 2016 to 2023. The findings indicate that the development of sustainable business models with a focus on value and social impact is an essential strategic step amid the complexity of economic, social, and environmental challenges. The implementation of these strategies is not only a moral responsibility for companies but also an urgent necessity in the face of rapid global changes. Engaging various aspects, including economic, social, and environmental dimensions, several key points need emphasis, namely the integration of sustainable values, technological and product innovation, stakeholder collaboration and engagement, employee development, and performance reporting and accountability.